Manipulating spin polarization of titanium dioxide for efficient photocatalysis - Lun Pan (Nature Portfolio, 2020)
Photocatalyst activity depends significantly on the material’s electronic structures. Here, authors manipulate the electron spin polarization of TiO2 by tuning the concentration of Ti vacancies and show improved photocatalytic activities.